1999
DOI: 10.1016/s0030-4018(98)00658-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantum photon emission from a moving mirror in the nonperturbative regime

Abstract: We consider the coupling of the electromagnetic vacuum field with an oscillating perfectlyreflecting mirror in the nonrelativistic approximation. As a consequence of the frequency modulation associated to the motion of the mirror, low frequency photons are generated. We calculate the photon emission rate by following a nonperturbative approach, in which the coupling between the field sidebands is taken into account. We show that the usual perturbation theory fails to account correctly for the contribution of T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The effect of photon production from vacuum, caused by single mirrors moving in the three-dimensional space with relativistic velocities or with great accelerations, was studied in the papers [181][182][183][184][185][186]. The nonrelativistic motion of the plane mirror was considered in [187][188][189][190][191]. The radiation from dynamically deforming mirrors with different boundary conditions was calculated in [192][193][194].…”
Section: Single Mirror Dcementioning
confidence: 99%
“…The effect of photon production from vacuum, caused by single mirrors moving in the three-dimensional space with relativistic velocities or with great accelerations, was studied in the papers [181][182][183][184][185][186]. The nonrelativistic motion of the plane mirror was considered in [187][188][189][190][191]. The radiation from dynamically deforming mirrors with different boundary conditions was calculated in [192][193][194].…”
Section: Single Mirror Dcementioning
confidence: 99%
“…For the most recent achievements in this field and references to other works see, e.g. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] (the problems of the classical electrodynamics with moving boundaries were studied, e.g. in [24,25]).…”
Section: Introductionmentioning
confidence: 99%
“…For ω 1 /2π = 10 GHz (corresponding to a distance between the plates of the order of several centimeters) we get 600 photons/sec. This number can be significantly increased in a 3D cavity, due to the exponential law (202). For the same frequency ω 0 /2π = 10 GHz, the maximal value of parameter µ = γω 0 t equals µ max ∼ 600t, time t being expressed in seconds.…”
Section: Discussionmentioning
confidence: 99%
“…Using the spectral approach, the authors of [200] showed that the radiation can be essentially enhanced under the resonance conditions (by the orders of magnitude, comparing with the case of a single mirror). The problem of the photon generation by a single perfectly reflecting mirror performing a bounded nonrelativistic motion was studied in [201,202], where the effects of polarization have been taken into account, and the spectral and angular distributions of the emitted photons have been found. Arbitrary space-time deformations of a single moving mirror have been treated in [203,204] with the aid of the pathintegral approach.…”
Section: Quantum Fields In the Presence Of Moving Boundariesmentioning
confidence: 99%